analysing the price discovery function of crude palm oil futures (fcpo) before and after shari'ah-compliance - Ahmad, Noryati (Asian Academy of Management (AAM), 2015)
This paper examines the price discovery function of Malaysian crude palm oil futures (FCPO) before and after Shari'ah-compliance. The sample used in the study is composed of crude palm oil futures (FCPO) and crude palm oil (CPO) prices for the January 2007 until December 2011 period. The period is divided into two sub-periods: Period I (January 2007–July 2009) before Shari'ah-compliance and Period II (August 2009– December 2011) after Shari'ah-compliance. The results of the Augmented Dickey Fuller (ADF) and Philips Perrons (PP) unit root tests suggest that the CPO and FCPO series are integrated at first difference. Johansen's co-integration test indicates that FCPO and its underlying spot market (crude palm oil) for both periods are co-integrated, implying that there is a causal relation between the two markets. In period I, the estimated results of Vector Error Correction model (VECM) indicate a one-way causality direction from the CPO market to the FCPO market in the long run. This can be interpreted as a price discovery process that occurs from its underlying spot market to the FCPO market. Furthermore, the study observes that the price discovery function of the crude palm oil futures market is increasingly more prominent after the Shari'ah Advisory Board (SAC) classified the product as Shari'ah-compliant (Period II)